Improving Teaching Skills Through Microteaching Training for PG PAUD UNINUS Students (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Teaching skills are the main competencies that must be possessed by PG PAUD students as prospective professional educators at the early childhood education level. However, there are still obstacles in terms of preparing lesson plans, mastering the class, and using appropriate learning media. This community service activity aims to improve the teaching skills of PG PAUD students at Universitas Islam Nusantara (UNINUS) through microteaching training. The implementation method includes stages: planning, theory delivery, teaching practice, and evaluation. The training was conducted in a participatory manner, where each participant practiced teaching in front of a small group and obtained direct feedback from the facilitator and peers. The results showed a significant improvement in the ability to develop lesson plans, use media, as well as communication techniques and classroom management. Participants also claimed to be more confident and ready to face real learning challenges in PAUD. In conclusion, microteaching training proved effective in developing students' teaching skills, so this activity is recommended to be carried out in a sustainable manner and become part of practical learning in higher education.